Red Blood Cell Aggregation Characterization: Quantification and Modeling Implications of Red Blood Cell Aggregation at Low Shear Rates - Mehri, Rym (Université d'Ottawa / University of Ottawa, 2016)
Red blood cells (RBCs) are the most abundant cells in human blood, representing 40 to 45% of the blood volume (hematocrit). These cells have the particular ability to deform and bridge together to form aggregates under very low shear rates. The theory and mechanics behind aggregation are, however, not yet completely understood. The purpose of this work is to provide a novel method to analyze, understand and mimic blood behaviour in microcirculation. The main objective is to develop a methodology to quantify and characterize RBC aggregates and hence enhance the current understanding of the non-Newtonian behaviour of blood at the microscale. For this purpose, suspensions of porcine blood and human blood are tested in vitro in a Poly-di-methylsiloxane (PDMS) microchannel to characterize RBC aggregates within these two types of blood. These microchannels are fabricated using standard photolithography methods. Experiments are performed using a micro Particle Image Velocimetry ( PIV) system for shear rate measurements coupled with a high speed camera for the flow visualization. Corresponding numerical simulations are conducted using a research Computational Fluid Dynamic (CFD) solver, Nek5000, based on the spectral element method solution to the incompressible non-Newtonian Navier-Stokes equations. RBC aggregate sizes are quantified in controlled and measurable shear rate environments for 5, 10 and 15% hematocrit. Aggregate sizes are determined using image processing techniques. Velocity fields of the blood flow are measured experimentally and compared to numerical simulations using simple non-Newtonian models (Power law and Carreau models). This work establishes for the first time a relationship between RBC aggregate sizes and corresponding shear rates in a microfluidic environment as well as one between RBC aggregate sizes and apparent blood viscosity at body temperature in a microfluidic controlled environment. The results of the investigation can be used to help develop new numerical models for non-Newtonian blood flow, provide a better understanding of the mechanics of RBC aggregation and help determine aggregate behaviour in clinical settings such as for degenerative diseases like diabetes and heart disease.
Keywords: red blood cell aggregation; erythrocytes; aggregate sizes; non-Newtonian; spectral element method; microchannel; micro PIV; blood viscosity